Effect of thermomechanical processing on the mechanical biofunctionality of a low modulus Ti-40Nb alloy. (January 2017) - Helth, A.; Pilz, S.; Kirsten, T.; Giebeler, L.; Freudenberger, J.; Calin, M.; Eckert, J.; Gebert, A.
Abstract: Different hardening strategies were evaluated regarding their potential to improve the mechanical biofunctionality of the cast and solution-treated low modulus β-Ti alloy Ti 40Nb. The strategies are based on thermomechanical treatments comprised of different hot- and cold-rolling steps, as well as annealing treatments aiming at the successive exploitation of different hardening mechanisms (grain boundary hardening, work hardening and precipitation hardening). Quasi-static tensile testing revealed that grain refinement by one order of magnitude has only a small impact on improving the mechanical biofunctionality of Ti-40Nb. However, work hardening effectively improves the tensile strength by 30% to a value of 650 MPa, while retaining Young׳s modulus at 60 GPa. The α-phase precipitation hardening was verified to have an increasing effect on both, strength and Young׳s modulus. Thereby, the change of Young׳s modulus dominates the change of the strength, even at low α-phase fractions. The pseudo-elastic behavior of Ti 40Nb is discussed under consideration of the microstructural changes due to the thermomechanical treatment. The texture changes evolving upon cold-rolling markedly influence the recrystallization behavior. However, the present results do not show a significant effect of the texture on the mechanical properties of Ti-40Nb.